Current status of the plant phosphorylation site database PhosPhAt and its use as a resource for molecular plant physiology - Arsova, Borjana; Schulze, Waltraud X. (Frontiers in Plant Science, 2012)
As the most studied post-translational modification protein phosphorylation is part of a growing number of proteomic studies. But these approaches generate large datasets from which, the specific spectrum based data can be hard to find. In 2007 the PhosPhAt database made it its goal to collect and present Arabidopsis phosphorylation data from and for the scientific community. At present, PhosPhAt 3.0 consolidates phosphoproteomics data from 19 published studies. 5460 Unique phosphoproteins are listed, about 25% of which have been identified in at least two independent experimental setups. The valuable data set encompasses over 13205 unique phosphopeptides, with unambiguous mapping to Serine (77%) Theronine (17%) and Tyrosine (6%). Sorting the functional annotations of experimentally found phosphorylated proteins in PhosPhAt, using Gene Ontology terms, shows an over representation of proteins in regulatory and signaling processes. Similar distribution is found when the PhosPhAt predictor, trained on experimentally obtained plant data, is used to predict phosphorylation sites for the Arabidopsis genome. Finally, the possibility to insert a protein sequence into the PhosPhAt predictor allows species independent use of the resource. In practice, we found that PhosPhAt allows easy exploitation of proteomic data for designing further experiments, and will demonstrate this on the example of targeted analysis of protein phosphorylation.